Use-Case 2.0. - JACOBSON, IVAR; SPENCE, IAN; KERR, BRIAN (Communications of the ACM, 2016)
The article explores the role of Use-Case 2.0 in connecting aspects of software development for better user experience. Topics discussed are the idea of slicing a use case to become suitable backlog items, basic principles of any successful application of use cases, and concepts to work with including use case, use-case slice and the story. Various applications of use cases are highlighted including user-intensive systems and software development approaches.